Elucidation of delignification promotion mechanism by soda cooking with addition of anthraquinone derivative using phenolic β-O-4-type lignin model oligomer - Ke Luo; Taiki Nishimoto; Yasuyuki Matsushita (Journal of Wood Science)
Abstract Using an artificial lignin model oligomer containing only the β-O-4 substructure, we investigated the mechanism, whereby the addition of an anthraquinone derivative (2-ethylanthraquinone; 2-EAQ) promotes pulping during alkaline cooking. Heteronuclear single quantum coherence nuclear magnetic resonance (HSQC NMR) analysis of the reaction products after cooking revealed that an enol ether signal appeared in the spectrum of the product without 2-EAQ, whereas it was not detected in the product with 2-EAQ. This result implies that the reduced type of 2-EAQ (2-ethylanthrahydroquinone, 2-EAHQ) attacked the lignin model oligomer, which promoted β-ether cleavage during soda cooking and reduced the elimination of γ-OH to form enol ether. When 2-EAQ was added, coniferyl alcohol was detected in the black liquor, confirming the reductive degradation of the lignin model oligomer by 2-EAHQ. Surprisingly, the degradation of the lignin model oligomers was accelerated, even in the absence of carbohydrates. Vanillic acid (VA) and ferulic acid (FA) were detected in the degradation products of the lignin model oligomer, suggesting that 2-EAQ oxidized not only the carbohydrates but also the degradation products to form 2-EAHQ.